A PRELIMINARY REPORT ON CORDIERITE-BEARING ASSEMBLAGES FROM RUNDVAGSHETTA, LUTZOW-HOLM BAY, EAST ANTARCTICA : EVIDENCE FOR A DECOMPRESSIONAL P-T PATH? - カワサキ, トシスケ; イシカワ, マサヒロ; モトヨシ, ヨウイチ; KAWASAKI, Toshisuke; ISHIKAWA, Masahiro; MOTOYOSHI, Yoichi (National Institute of Polar Research, 1993)
P(論文) Diagnostic mineral assemblages involving cordierite, sapphirine, orthopyroxene, sillimanite and garnet are newly reported from Rundvagshetta, Lutzow-Holm Bay, East Antarctica. Cordierite is probably of secondary origin, because it occurs as symplectitic intergrowth with sapphirine at the expense of initial orthopyroxene+sillimanite. In a different domain, vermiculated orthpyroxene+cordierite±sapphirine replaces initial garnet locally. On the basis of the textures, the following reactions are inferred : orthopyroxene+sillimanite+quartz=cordierite, orthopyroxene+sillimanite=cordierite+sapphirine, garnet+quartz=orthopyroxene+cordierite, garnet=orthopyroxene+cordierite+sapphirine. These reactions suggest near isothermal decompression in the model FMAS system, and along with a prograde kyanite from the same locality, the clockwise P-T path of the rocks are confirmed. Moreover, the maximum temperature condition of the Lutzow-Holm Complex is estimated to be as high as 900℃ based on the initial orthopyroxene+sillimanite+garnet assemblage, and this value is apparently higher than those previously estimated. In high-grade metamorphic terranes of East Antarctica, the similar mineral assemblages and reaction textures have been reported from Forefinger Point in Enderby Land and the Rauer Group in Prydz Bay, respectively. However, it is questionable as to whether these terranes can be corrrelatable to Rundvagshetta, because no evidence of prograde P-T paths have been obtained from Forefinger Point and the Rauer Group and there is a lack of relavent geochronological data. departmental bulletin paper